Immunohistochemical expression analysis of MMP-1, TIMP-2 and p53 in Barrett’s esophagus, dysplasia and esophageal adenocarcinoma - García-Varona, Alejandro; Fernández-Vega, Iván; Santos-Juanes, Jorge (Polish Journal of Pathology, 2021)
Barrett’s esophagus (BE) is the most important risk factor for the development of esophageal adenocarcinoma. It develops through a progressive sequence of histologic and molecular events that begin with metaplasia and then progresses through various stages of dysplasia. Matrix metalloproteinases are involved in the degradation of the extracellular matrix and play an important role in tumor progression. The immunohistochemical expression of MMP-1, TIMP-2 and p53 in 111 samples from 45 patients diagnosed with BE with and without dysplasia and adenocarcinoma of the esophagus was retrospectively studied, and statistical analysis was conducted to measure the association between their expression and the degree of dysplasia present. MMP-1 was expressed in 33.3% of the samples studied, mainly in the adenocarcinoma subgroup with up to 40% positive cases (p = 0.494). In contrast, TIMP-2 was expressed in 25.2% of the samples, and no positive cases were identified in the adenocarcinoma subgroup (p = 0.037). Aberrant p53 expression was observed in 81.4% of the samples diagnosed with some degree of dysplasia (p < 0.001). MMP-1 showed no statistically significant differences between diagnostic entities. A statistically significant loss of TIMP-2 expression was observed in distal esophageal adenocarcinoma samples, which contrasts with the aberrant expression of p53 in dysplastic cases.